Effects of Primary Welding Parameters on FCAW Steel Weld Form - (:unkn) unknown (My University, 2018)
Flux Cored Arc Welding (FCAW) has been a viable welding process for structural steel erection, heavy equipment repair, bridgeconstruction and other similar applications. The primary welding parameters (welding current, welding speed and arc voltage) determineFCAW weld geometry, weld mechanical properties and weld quality. In this study bead on plate welds were produced on SAE 1015steel work pieces. Metallographic investigations were done on the cross-sectional of the welds. The effects of the primary weldingparameters on weld components (penetration depth, reinforcement height, width, reinforcement contact angle, reinforcement area and penetration area) were measured. The effects of primary welding parameters on weld bead geometry are presented in graphical forms.

Özlü tel ark kaynağı yüksek ergime gücü ve yüksek kaliteli dikiş üretme özelliğine sahip olduğundan kullanımı sürekli artmaktadır. Bu özelliklerin korunması için özlü tel ark kaynağı parametrelerinin yakından kontrol edilmesi gerekmektedir. Kaynak akımı ve kaynak geriliminin etkisini ortaya çıkarmak için alaşımsız çelik levhalar üzerine özlü tel ark kaynak yöntemi ile kör dikişler çekilmiştir. Dikişlerin genişlik, nüfuziyet ve taşıma yükseklikleri, eriyen ve yığılan metal kesit alanları ile dikiş yüzeyi açıları ölçülmüştür. Her kaynak parametresinin dikiş geometri boyutları üzerindeki tesirini ortaya çıkaran grafikler çizilmiştir.
Birincil Kaynak Parametrelerinin FCAW Çelik Kaynak Formuna Etkileri
Keywords: Astronomi ve Astrofizik; Biyoloji; Kimya, Analitik; Kimya, Uygulamalı; Kimya, İnorganik ve Nükleer; Kimya, Tıbbi; Kimya, Organik; Fizikokimya; Çevre Bilimleri; Genetik ve Kalıtım; Matematik; Mantar Bilimi; Optik; Paleontoloji; Fizik, Uygulamalı; Fizik, Atomik ve Moleküler Kimya; Fizik, Katı Hal; Fizik, Akışkanlar ve Plazma; Fizik, Matematik; Fizik, Nükleer; Fizik, Partiküller ve Alanlar; Viroloji; Su Kaynakları